Suppression of costimulation by human cytomegalovirus promotes evasion of cellular immune defenses - Wang, Eddie C Y; Pjechova, Mariana; Nightingale, Katie; Vlahava, Virginia-Maria; Patel, Mihil; Ruckova, Eva; Forbes, Simone K; Nobre, Luis; Antrobus, Robin; Roberts, Dawn; Fielding, Ceri A; Seirafian, Sepehr; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2018)
CD58 is an adhesion molecule that is known to play a critical role in costimulation of effector cells and is intrinsic to immune synapse structure. Herein, we describe a virally encoded gene that inhibits CD58 surface expression. Human cytomegalovirus (HCMV) UL148 was necessary and sufficient to promote intracellular retention of CD58 during HCMV infection. Blocking studies with antagonistic anti-CD58 mAb and an HCMV UL148 deletion mutant (HCMV∆UL148) with restored CD58 expression demonstrated that the CD2/CD58 axis was essential for the recognition of HCMV-infected targets by CD8+ HCMV-specific cytotoxic T lymphocytes (CTLs). Further, challenge of peripheral blood mononuclear cells ex vivo with HCMV∆UL148 increased both CTL and natural killer (NK) cell degranulation against HCMV-infected cells, including NK-driven antibody-dependent cellular cytotoxicity, showing that UL148 is a modulator of the function of multiple effector cell subsets. Our data stress the effect of HCMV immune evasion functions on shaping the immune response, highlighting the capacity for their potential use in modulating immunity during the development of anti-HCMV vaccines and HCMV-based vaccine vectors.
Keywords: Cytomegalovirus Infections; transformované buněčné linie; imunitní únik; cytomegalovirové infekce; lidé; CD8-Positive T-Lymphocytes; Cytomegalovirus; Immune Evasion; Killer Cells, Natural; buňky NK; Humans; Viral Fusion Proteins; buněčná imunita; Cell Line, Transformed; proteiny virové fúze; CD8-pozitivní T-lymfocyty; Immunity, Cellular